Satisfaction at ifes: an analysis through career anchors / Satisfação no ifes: uma análise por meio das âncoras de carreira - Rosângela C. Vargas; Aridelmo Teixeira (RAM. Revista de Administração Mackenzie, 2018)
Purpose: The objective of this research is to analyze the job satisfaction of public servants through career anchors. Originality/value: The contribution of this research is to apply a collection instrument in reduced version for the analysis of job satisfaction in the public service in the search of subsidies for proposals of improvements in work processes related to people management. Design/methodology/approach: We conducted the research with 671 public servants from the public education area. As an instrument of collection, we sent questionnaires using the electronic survey method and on paper. We based the questionnaire on the “Career Anchor Inventory” - adapted by Igbaria and Baroudi (1993) and the work by Netemeyer, Boles, and McMurrian (1996), termed as “Global Job Satisfaction”. Findings: The Security/Stability anchor obtained significant explanatory power with job satisfaction, but its representativeness was not the largest in the sample. Our practical contribution will be in the support to the construction of policies of people management, since the results indicated lower rates of satisfaction with regard to the aspects of promotion and with respect to the relationship with senior management. Objetivo: O objetivo desta pesquisa é analisar a satisfação no trabalho dos servidores públicos por meio das âncoras de carreira. Originalidade/relevância: A contribuição desta pesquisa é aplicar um ins trumento de coleta em versão reduzida para análise da satisfação no trabalho no serviço público na busca de subsídios para propostas de melhorias nos processos de trabalho relacionados à gestão de pessoas. Principais aspectos metodológicos: A pesquisa foi realizada com 671 servidores de uma autarquia da área de ensino público. Como instru mento de coleta foi utilizado questionário enviado por e-mail, método de survey eletrônico e em papel. O questionário foi baseado no “Inven tário de Âncora de Carreira”- adaptada por Igbaria e Baroudi (1993) e no trabalho de Netemeyer et al. (1996), denominado “Satisfação Global no Trabalho”. Síntese dos principais resultados: Os resultados apresentados identi ficaram que a âncora Segurança/Estabilidade foi relacionada com satisfação no trabalho tanto para os servidores docentes quanto para os administrativos, enquanto a âncora Serviço/Dedicação, a uma Causa só, foi relacionada para os servidores administrativos. A pesquisa tam bém identificou baixa representatividade de indivíduos com a âncora Competência Gerencial.